2007
DOI: 10.1103/physrevb.75.235201
|View full text |Cite
|
Sign up to set email alerts
|

Vacancy generation in liquid phase epitaxy of Si

Abstract: Concerted experiments and theoretical analysis are applied to conclusively demonstrate the vacancy generation during fast melting and regrowth of Si by laser irradiation. Experiments, based on the positron annihilation spectroscopy and designed to test the theoretical predictions, evidence a vacancy supersaturation after the laser process depending on the irradiation conditions. Stochastic atomistic simulations of the molten Si recrystallization show trapping of vacancies in the recrystallized region. Finally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…13 The fact that no vacancies are detected due to LTA alone is quite surprising; in particular, it is different from Si wherein V generation and clustering caused by pulsed laser irradiation has been observed. 17 Milazzo et al 18 arrived at the same conclusion based on the changes from the oxygeninduced strain measured in virgin Ge and attributed to interstitial occupation. In their study, the doped samples showed negligible O contribution to the strain, which was associated with vacancy-oxygen complexes, while O itself was found uncorrelated with the As passivation.…”
mentioning
confidence: 60%
“…13 The fact that no vacancies are detected due to LTA alone is quite surprising; in particular, it is different from Si wherein V generation and clustering caused by pulsed laser irradiation has been observed. 17 Milazzo et al 18 arrived at the same conclusion based on the changes from the oxygeninduced strain measured in virgin Ge and attributed to interstitial occupation. In their study, the doped samples showed negligible O contribution to the strain, which was associated with vacancy-oxygen complexes, while O itself was found uncorrelated with the As passivation.…”
mentioning
confidence: 60%
“…It is reported that melting induced by laser irradiation on c-Si substrate generates a supersaturation of vacancies at the maximum melt depth [6]. The vacancies are trapped in the recrystallized region as confirmed by the positron annihilation spectroscopy [7]. By matching the maximum laser melt depth where the vacancies are created with the location of the EOR defects at the PAI depth, boron TED is significantly suppressed with considerable reduction in the EOR defects [8].…”
Section: Introductionmentioning
confidence: 89%
“…Therefore, this greatly reduces the amount of excess interstitials remaining in the interstitial positions as EOR defects. From the kinetic lattice Monte Carlo simulation results reported by La Magna et al [7], the net vacancy density trapped within the Si substrate is at a concentration of 10 16 cm −3 , and it saturates at a level of 10 17 cm −3 . Thereby, the estimated amount of EOR defects being reduced is also in the concentration of 10 16 −10 17 cm −3 .…”
Section: Device Fabricationmentioning
confidence: 97%
“…In other cases the experimental data sets may be used for the LKMC model calibration. It is also possible that the LKMC results themselves are used for the calibration of macroscopic simulation models such as the kinetics phase field model used to simulate the depth distribution of the vacancy-type defects arising from the multishot laser irradiation of a Si substrate [14].…”
Section: Introductionmentioning
confidence: 99%
“…LKMC methods are used to simulate the vast variety of solid transformation kinetics such as e.g. shape relaxation of nanoclusters [12], evolution of the defect structure in solid [13] and laser melted Si [14], vacancy mediated interdiffusion in SiGe alloys [15], step flow growth and defect generation of SiC [16,17], hydrogen adatom [18,19] and vacancy defect [20] evolution in graphene, etc. LKMC modeling can be applied to reveal general peculiarities of a particular process.…”
Section: Introductionmentioning
confidence: 99%